Zearalenone exposure mediated hepatotoxicity via mitochondrial apoptotic and autophagy pathways: Associated with gut microbiome and metabolites. (October 2021) - Li, Yuanliang; Yi, Jiangnan; Zeng, Qiwen; Liu, Yingwei; Yang, Bijing; Liu, Bingxian; Li, Yangwei; Mehmood, Khalid; Hussain, Riaz; Tang, Zhaoxin; Zhang, Hui; Li, Ying
Graphical abstract: Highlights: Exposure to the Zearalenone results in hepatotoxicity, which altered liver function and damage liver structure. Zearalenone exposure induced apoptosis and autophagy in hepatocytes via mitochondrial apoptosis and Beclin1 autophagy signaling pathway. Zearalenone significantly altered the variation of 91 metabolites, which mainly involved in glycerophospholipid metabolism pathway. Zearalenone affect the liver via interaction of gut microbiome and metabolites. Abstract: Zearalenone (ZEN), a mycotoxin is frequently detected in different food products and has been widely studied for its toxicity. However, the underlying mechanisms of hepatotoxic effects, relationship between gut microbiome and liver metabolite mediated hepatotoxicity mechanisms induced by ZEN are still not clear. Here, we reported that the different microscopic changes like swelling of hepatocyte, disorganization of hepatocytes and extensive vacuolar degeneration were observed, and the mitochondrial functions decreased in exposed mice. Results exhibited up-regulation in expression of signals of apoptosis and autophagy in liver of treated mice via mitochondrial apoptotic and autophagy pathway (Beclin1/p62). The diversity of gut microbiome decreased and the values of various microbiome altered in treated mice, including 5 phyla (Chloroflexi, Sva0485, Methylomirabilota, MBNT15 and Kryptonia) and genera (Frankia, Lactococcus, Anaerolinea, Halomonas and Sh765B-TzT-35) significantly changed. Liver metabolism showed that the concentrations of 91 metabolite including lipids and lipid like molecules were significantly changed. The values of phosphatidylcholine, 2-Lysophosphatidylcholine and phosphatidate concentrations suggestive of abnormal glycerophosphate metabolism pathway were significantly increased in mice due to exposure to ZEN. In conclusion, the findings suggest that the disorders in gut microbiome and liver metabolites due to exposure to ZEN in mice may affect the liver.